The epidemiology of traumatic brain injuries in the fastest-paced city in China: a retrospective study - Zou, Jun-feng; Fang, Hai-lan; Zheng, Jing; Ma, Yu-qiang; Wu, Chu-wei; Su, Gao-jian; Liu, Xian-sheng; Liu, Jun; Gao, Jie; Zhang, Jie-hua; Zhu, Dong-liang; Shi, Xin; et al. (Frontiers in Neurology, 2023)
Introduction Traumatic brain injury (TBI) seriously affects the quality of human health and the prognosis of the patient, but the epidemiological characteristics of TBI can vary among populations. Numerous changes have occurred in the epidemiological characteristics of individuals with TBI in the fast-paced city of Shenzhen, China. However, little is known about these characteristics. This study aimed to investigate the changes in TBI epidemiology, help clinicians improve medical treatment. Methods In this retrospective cross-sectional analysis, we collected the data of 4,229 patients with TBI admitted to 20 hospitals in Shenzhen in 2017. We collected data on age, gender, cause and severity of the injury, eventual diagnosis, time from injury to admission in a neurosurgery department, and patient outcomes. Two neurosurgeons simultaneously collected the data. We compared these results with a similar study conducted in Shenzhen during the period from 1994 to 2003 to clarify and explain the changes in the epidemiological characteristics of TBI. Results The majority of respondents were men [2,830 (66.9%)]. The mean age was 32.5 ± 21.4 years. The youngest patient was less than 1 year old, and the oldest patient was 101 years old. A total of 3,947 (93.3%) patients had a favorable outcome, 219 (5.2%) had an unfavorable outcome, and 63 (1.5%) died. The predominant external cause was falls (1,779 [42.1%]); this was the most common cause of TBI in children and older adults. Riders of electric bicycles (423 [29.0%]) were the most vulnerable to traffic accident-related injuries. Time greater than 50 h from injury to admission to a neurosurgical department had a significant effect on prognosis (p < 0.001). Conclusion The epidemiological characteristics of TBI have changed significantly over the past 20 years. Falls, rather than traffic accidents, were the most common cause of TBI. Further research is needed to devise solutions to decrease the incidence of falls and improve the outcomes of TBI.